Retinal nerve fibre layer assessment in myopic glaucomatous eyes: comparison of GDx variable corneal compensation with GDx enhanced corneal compensation. Issue 10 (29th July 2008) - Morishita, S; Tanabe, T; Yu, S; Hangai, M; Ojima, T; Aikawa, H; Yoshimura, N
Abstract : Aim: To compare the results of scanning laser polarimetry (GDx) with variable corneal compensation (VCC) and enhanced corneal compensation (ECC) when applied to myopic glaucomatous eyes. Methods: Forty glaucoma eyes with moderate myopia (between −3 and −6 D) and 35 glaucoma eyes with high myopia (−8 D or greater) were enrolled in this study. GDx VCC, GDx ECC and standard automated perimetry (SAP) were performed. The prevalence of an atypical retardation pattern (ARP), the typical scan score (TSS) and retinal nerve fibre layer (RNFL) thickness were compared between VCC and ECC in both groups of myopic subjects. A correlation analysis between RNFL thickness and visual sensitivity was also conducted. Results: In both myopic groups, the mean TSS is significantly lower (p<0.0001), and the prevalence of ARP was significantly higher (p<0.0001) by VCC scans than by ECC scans. Temporal, superior, nasal, inferior, temporal (TSNIT) average and temporal average thickness showed significantly higher values (p<0.001) by VCC than by ECC. A statistically significant association was observed between TSNIT average and mean deviation of SAP by ECC scan. Conclusions: ECC scans showed a better retardation pattern and structure–function relationship than did VCC, and ECC appeared to be more suitable for RNFL assessment in glaucomatous eyes that are moderately to highly myopic.